Role of bone marrow imprint smear cytology as a bridge between bone marrow aspiration and biopsy in children with pancytopenia - S., Spoorthi M.; Rudramurthy, Pradeep; Raghunathan, Poornima; Saif, Hafsa; Lokanath, Hemalata (International Journal of Contemporary Pediatrics, 2024)
Background: Bone marrow aspiration cytology (BMA), bone marrow biopsy (BMB) and bone marrow Touch imprint smear cytology (BMI) are three important modalities helpful in arriving at a diagnosis in pancytopenia cases. BMA gives cytological picture; BMI plays a pivotal role in providing early diagnosis while awaiting BMB. Hence, the present study was undertaken to assess the role of BMI to bridge the gap between BMA and BMB. Methods: 40 children from one to eighteen years with pancytopenia to Indira Gandhi Institute of Child Health, Bengaluru, over a period of one year from September 2022 to August 2023 were enrolled. They were subjected to routine investigations, followed by BMA and BMB. Imprint smears were made from the biopsy core and examined. Results: BMA was useful in arriving at a diagnosis in 83.3% of cases, BMI smear examination and BMB were diagnostic in 91.6% and 95.8% of cases respectively. Most common entity in age group of 1-6 years was hemophagocytic lympho histiocytosis (HLH) followed by aplastic anaemia (AA) and megaloblastic anaemia (MA) in 6-12 years and 12-18 years age group children respectively. Conclusions: This study concludes that better results were yielded when all the three procedures were performed simultaneously. BMI was a useful diagnostic modality while awaiting biopsy. In cases where there was dry tap or hemodilution in BMA, the imprint smear cytology helped in rendering early diagnosis than BMB. Hence, this study emphasizes that BMI cytology should be implemented as a mandatory practice during bone marrow evaluation.